Mindfulness and its relationship to the quality of academic life in the light of distance education on a sample of master's students at Taif University - Alomari, Esraa Saad; Hella, Azza Mohammed Abdu (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the mental alertness and its relationship to the quality of academic life among a sample of master’s students at Taif University، and to reveal the differences in the level of mental alertness and the quality of academic life among the sample members that are due to the gender variable. and the study used the relational descriptive approach، and the sample consisted of (100) male and female students from the master’s level at Taif University. The tools used included the mental alertness scale prepared by “Pierre et al.” translated and Arabized by Abdul Rahman (2006)، and the academic quality of life scale prepared by Al-Otaibi (2014)، and the study reached the following results: There is a relationship: Correlation between some dimensions of mental alertness and its total degree with some dimensions of quality of academic life and its total score، there are no statistically significant differences between the average responses of the study sample in the dimensions of the vigilance scale (observation، awareness behavior، not making judgments، not issuing reactions) and degree The totality of the scale is attributed to the gender variable. There are statistically significant differences between the average responses of the study sample in the dimensions of the academic quality of life scale (knowledge، dexterity، personality، judgment The total score of the scale is attributed to the gender variable، and the study ended with a few recommendations: Including activating the role of psychological counselors in universities to accompany students and give them mental alertness to improve the quality of their academic lives.
Keywords: Mindfulness; Quality of academic life; Online education; master's students at Taif University